Strategi Marketing Public Relations Nasi Kebuli Al-Khalid dalam Meningkatkan Brand Image - Ryvaldo Fernando; Riza Hernawati (Bandung Conference Series: Public Relations, 2024)
Abstract. Due to high competition at this time, entrepreneurs are indirectly required to make optimal and maximum efforts to improve the quality, taste and products produced. These efforts are made to ensure that the business meets expectations, fulfills its goals, and presents a positive image to the public. Marketing Public Relations is an action to establish communication between companies and consumers. Marketing public relations has 3 strategies, namely pull strategy, push strategy, pass strategy. The purpose of this research is to determine the strategies used by the marketing and public relations department of Nasi Kebuli Al-Khalid to improve its brand image. Descriptive methodology with interview data was used in this research. Based on the research results, Nasi Kebuli Al-Khalid's pull strategy is carried out through publications as an effort to convey information to consumers and is carried out online through websites, social media and food ordering service applications. Apart from that, publication is carried out offline using banners or billboards when opening a new restaurant branch. The push strategy is carried out by carrying out promotions by providing discounts on food ordering service applications and offline by considering the image of "affordable prices, good taste and hygienic". Nasi Kebuli Al-Khalid's pass strategy is carried out by providing support for a religious activity (sponsorship) in the form of financial support and food. This support does not seek profit, only provides support voluntarily and this is often done because the image that Nasi Kebuli Al-Khalid wants to display is not only "good taste, affordable price and hygienic" but also the public wants to see that Nasi Kebuli Al-Khalid is an "Islamic" restaurant. Abstrak. Tingginya persaingan pada saat ini, para pengusaha secara tidak langsung dituntut untuk berupaya lebih optimal dan semaksimal mungkin dalam meningkatkan kualitas, rasa, dan produk yang dihasilkan. Marketing Public Relations sebagai salah satu tindakan untuk menjalin komnuikasi antara perusahaan dan konsumen. Marketing public relations memiliki 3 strategi yaitu pull strategy, push strategy, pass strategy. Tujuan dari penelitian ini adalah untuk mengetahui strategi yang digunakan oleh bagian pemasaran dan humas Nasi Kebuli Al-Khalid untuk meningkatkan citra mereknya. Metodologi deskriptif dengan data wawancara digunakan dalam penelitian ini. Berdasarkan hasil penelitian, pull strategy Nasi Kebuli Al-Khalid dilakukan dengan publikasi sebagai upaya menyampaikan informasi kepada konsumen dan dilakukan secara online melalui website, media sosial, dan aplikasi layananan pemesanan makanan. Selain itu, publikasi dilakukan secara offline dengan menggunakan umbul-umbul atau baliho pada saat akan melakukan opening di cabang restoran baru. Push strategy dilakukan dengan melakukan promosi dengan pemberian potongan harga di aplikasi layanan pemesanan makanan dan secara offline dengan mempertimbangkan image ”harga terjangkau, rasa yang enak, dan higenis”. Pass strategy Nasi Kebuli Al-Khalid dilakukan dengan memberikan dukungan pada sebuah kegiatan keagaaman (sponsorship) dengan bentuk dukungan keuangan dan makanan. Dukungan tersebut tidak mencari keuntungan hanya memberikan dukungan secara sukarela dan hal tersebut sering dilakukan karena image yang ingin ditampilkan oleh Nasi Kebuli Al-Khalid bukan hanya ”cita rasa yang enak, harga terjangkau, dan higenis” akan tetapi juga ingin dipandang oleh masyarakat bahwa Nasi Kebuli Al-Khalid merupakan restoran ”Islami”.